Characteristics and Risk Factors for Suicide in People with Schizophrenia in Comparison to Those without Schizophrenia. (October 2021) - Lyu, Juncheng; Zhang, Jie; Hennessy, Dwight A.
Highlights: This study compares risk factors between suicides with and without schizophrenia. Risk factors for suicide include age, gender, physical health, and family factors. Schizophrenia suicides are linked to depression, anxiety, social support and past suicide behavior. Abstract: Background: Little research has been conducted that compares suicide cases with and without schizophrenia. The aim of the present study was to identify demographic, personal, social, relational, and psychological characteristics among suicides identified posthumously with schizophrenia compared to those without. Methods: The DSM-IV was used to independently assess the presence of schizophrenia among suicide cases by two psychiatrists. Data on risk factors was collected through a psychological autopsy method, which included structured interviews of two informants for each suicide case (a family member and a close friend). Interview questions included demographic characteristics, suicide risk factors, the Beck Hopelessness Scale, Dickman's Impulsivity Inventory, the Spielberger State-Trait Anxiety Inventory, the Hamilton Depression Scale and the Duke Social Support Inventory. Results: The prevalence of schizophrenia was 9.69% among suicide cases in this sample. The schizophrenia suicide group was more likely to be female, older, in poorer physical health, suffer from chronic disease, suffer other psychological disorders, and have a family history of psychological disorders compared to those not diagnosed schizophrenia. Other important risk factors included more frequent past suicide attempts, increased levels of depression and anxiety, lower levels of impulsivity, lower help seeking from friends, and lower social interaction social support. Conclusions: There is a notable link between schizophrenia and suicide in China. Identification of social, personal, relational, and psychological risk factors could beneficially guide attempts to improve future preventive measures against suicide among those with schizophrenia in China.